Electrical properties of porous silicon for humidity sensor application / Noorhazleena Azaman - Azaman, Noorhazleena (2008)
Porous silicon (PSi) is a promising material for electronics and sensors devices application. Electrical properties of porous silicon for sensor application were analyzed. The characterized on porous silicon layer by using photoluminescence (PL) and I-V measurement (I-V) has been done. Porous silicon was formed by electrochemical etching on p(100) type Si wafer substrate with the constant current density (20mA/cm ) and variable the etching time. The samples ware prepared under various etching time and properties of porous silicon depend on an etching time. Porous silicon has been used in humidity sensors to detect humidity through changes of its electrical properties. The samples of porous silicon were characterized by using Photoluminescence Spectroscopy (PL) that used to characterize optical properties while I-V Measurement (I-V) used to characterize porous silicon junction properties using a linear voltage source. The result shows PL intensity is increase while the wavelength is decrease for etching time of PSi is longer. For the I-V measurement result shows the PSi samples that exposed to ethanol give low resistance which allow current easily to flow through the PSi.